2019
DOI: 10.7554/elife.48118
|View full text |Cite
|
Sign up to set email alerts
|

Novel charged sodium and calcium channel inhibitor active against neurogenic inflammation

Abstract: Voltage-dependent sodium and calcium channels in pain-initiating nociceptor neurons are attractive targets for new analgesics. We made a permanently charged cationic derivative of an N-type calcium channel-inhibitor. Unlike cationic derivatives of local anesthetic sodium channel blockers like QX-314, this cationic compound inhibited N-type calcium channels more effectively with extracellular than intracellular application. Surprisingly, the compound is also a highly effective sodium channel inhibitor when appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 112 publications
(152 reference statements)
2
34
0
Order By: Relevance
“…5d) in which Ca Our data are consistent with the analgesic actions of locally applied combined inhibitors of Ca V 2.2 and Na V 1.7 channels in different mouse models of inflammatory pain. 24 While previous studies have focused almost exclusively on centrally located Ca V 2.2 channels, we show that peripheral Ca V 2.2 channels in skin are essential for thermal hyperalgesia, a [11] finding that may help explain previous findings. [32][33][34] For example, studies of KO mice show reduced hyperalgesia induced by formalin but in some of these studies, this occurs independent of effects on acute nociception.…”
Section: P2x7 Receptor Activation Induces Hyperalgesia Downstream Of supporting
confidence: 59%
See 2 more Smart Citations
“…5d) in which Ca Our data are consistent with the analgesic actions of locally applied combined inhibitors of Ca V 2.2 and Na V 1.7 channels in different mouse models of inflammatory pain. 24 While previous studies have focused almost exclusively on centrally located Ca V 2.2 channels, we show that peripheral Ca V 2.2 channels in skin are essential for thermal hyperalgesia, a [11] finding that may help explain previous findings. [32][33][34] For example, studies of KO mice show reduced hyperalgesia induced by formalin but in some of these studies, this occurs independent of effects on acute nociception.…”
Section: P2x7 Receptor Activation Induces Hyperalgesia Downstream Of supporting
confidence: 59%
“…18,19,42,64 Peripheral inhibition of Ca V 2.2 channels for analgesia Ca V 2.2 channels are important targets for the development of novel analgesics as evidenced by the initial clinical success of ω-conotoxin MVIIA as an analgesic in patients with otherwise intractable chronic pain. [3][4][5][6]68 Our data raise the possibility that local injection of ω-conotoxin MVIIA, or, as shown by others, dual inhibitors of Ca V 2.2 and Na V 1.7, 24 may have clinical utility against certain inflammatory responses, by interrupting signals locally, thereby avoiding severe, debilitating side-effects 3,6,9,69 that limit that current use of Ca V 2.2 channel blockers. 70 Intraplantar ω-conotoxin MVIIA was highly effective at inhibiting thermal hyperalgesia independent of effects on basal nociception, central Ca V 2.2 channels (Fig.…”
Section: Peripheral Ca V 22 Channels In Skin Required For Thermal Hymentioning
confidence: 94%
See 1 more Smart Citation
“…While not knowing which Ca 2+ channel is targeted by 1-O-acetylgeopyxin A is a limitation of this study, dual or multi-target antagonists may have a better efficacy profile. Along these lines, it was recently reported that a derivatized version of a cationic N-type calcium channel blocker inhibited CaV2.2 (N-type) calcium channels as well as both tetrodotoxin-sensitive and tetrodotoxin-resistant voltage-gated sodium channels and was highly effective in producing long-lasting analgesia in mouse models of surgical and inflammatory pain [29]. Further, the molecular action of gabapentinoids may involve the calcium channel auxiliary protein α2δ-1's action on CaV2.2 [30], thrombospondin [31], or Nmethyl-D-aspartate receptors [32], highlighting the potential of multi-target engagement to elicit analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…A manual Von Frey assay was used to assess mechanical sensitivity in mice before and after UV burn, as previously described (Lee et al, 2019). After mice were habituated to the testing cage (7.5 × 7.5 × 15 cm) with a metal grid floor for 45 min for 2 days, baseline values were measured using nine von Frey filaments with different bending forces (0.04, 0.07, 0.16, 0.4, 0.6, 1, 1.4, 2, and 4 g).…”
Section: Behavioral Measurements Of Sensory and Motor Functionmentioning
confidence: 99%